The Postnatal Growth Delay in Preterm Infants and Survey of the Risk Factors - Starets, Olena; Khimenko, Tetiana; Mykhaylenko, Veronica (Journal of Pediatric Biochemistry, 2016)
The aim was to analyze the factors that are associated with growth delay (GD) and malnutrition in preterm infants during the first year of life. The trial included 150 preterm children. The data of life history and anthropometry were studied. The trial showed statistically significant correlation of GD in preterm babies with intrauterine growth restriction, prolonged respiratory care and tube feeding, formula feeding, anemia of prematurity, and severe asphyxia at birth. To optimize health care in preterm infants, it is necessary to consider the factors that correlate with GD and give the recommendations how to prevent or treat pathological and deficit conditions.
Keywords: preterm infant; growth delay; risk factors